Results and Complications of Spinal Anesthesia in Percutaneous Nephrolithotomy - Mehrabi, Sadrollah; Karimzadeh Shirazi, Kambiz (Urology Journal, 2010)
Introduction: Percutaneous nephrolithotomy (PCNL) is the treatment of choice for large kidney calculi, staghorn calculi, and calculi that are multiple or resistant to shock wave lithotripsy. In many centers, PCNL is performed under general anesthesia. However, complications under spinal anesthesia can be less frequent. We evaluated the impact of spinal anesthesia on intra-operative and postoperative outcome in patients undergoing PCNL.Materials and Methods: The intra-operative and postoperative anesthetic and surgical outcomes were evaluated in 160 consecutive patients who underwent PCNL under spinal anesthesia in the prone position.Results: The mean age of the patients was 40.0 ±14.3 years, and the mean operative time was 95.0 ± 37.8 minutes. The mean calculus size was 34.2 ± 9.8 mm. Ten patients had staghorn calculi (mean size, 4.2 ± 1.1 cm; mean operative time, 140 ± 40 minutes). Return of sensory and motor activity took 140.0 ± 19.7 minutes and 121.0 ± 23.8 minutes, respectively. During the first part of anesthesia, 18 patients developed hypotension, which was controlled by ephedrine, 10 mg, intravenously. Ten patients (6.3%) needed blood transfusion and 6 complained of mild to moderate headache, dizziness, and mild low back pain for 2 to 4 days after the operation, which improved with analgesics and bed rest. Seventy percent of the patients had complete clearance of calculus or no significant residual calculi larger than 5 mm on follow-up ultrasonography. Conclusion: Spinal anesthesia is safe and effective for performing PCNL and is a good alternative for general anesthesia in adult patients.